Undergraduate and graduate studies programs in Social Work in Brazil / Graduação e pós-graduação em Serviço Social no Brasil - Garcia, Maria Lúcia Teixeira; Fernandez, Cristiane Bonfim (Textos & Contextos (Porto Alegre), 2018)
This article examines the expansion of undergraduate and graduate programs in Brazil, characterizing the convergences and divergences between the two educational levels in the last 15 years. This is a document study based on data available on the websites of the Ministry of Education and the Coordination for the Improvement of Higher Education Personnel (CAPES). Undergraduate studies in social work are currently offered by 575 institutions, distributed among Brazil’s five geographical regions, particularly in the Southeast and South. These institutions are for the most part private and provide both classroom-based and distance learning formats. Graduate studies programs continue to expand at a different pace. They are primarily linked to public institutions, with classroom-based teaching and a higher number of PhD holders among their professors.